Perencanaan Peningkatan Kualitas Jasa Pelayanan Perpustakaan Dengan Metode Rekayasa Nilai - Purwatiningsih, Dyah Retno (Jurnal Teknik Industri, 2000)
A quality of service in UPT. Centre Library Muhammadiyah University of Malang especially in user devision and human resources management division is one of most used division which is complaint by users and need to increase of quality to satisfy users. Value engineering is a method which solue this problem to increase the quality service with keeping the rule of customer satisfaction. Based on the analysis with implement value engineering can be found the initial value design about I and advised design about 1.045 in other hand the initial design performance give about 45,799 and advised design about 51,488. It means that there is an increasing 4.5 % of value and 12,421 % of performance.